2016
DOI: 10.5812/hepatmon.35058
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Knowledge, Individual Perceived Risk, General Perceived Risk, and Behavioral Intentions Regarding Hepatitis B among Students in the Faculty of Nursing, Midwifery and Health at Shahrekord Islamic Azad University in 2014

Abstract: BackgroundHepatitis B is the most common cause of liver disease, and medical students are a risk group for the disease given their future occupations.ObjectivesThe aim of the study was to assess of predictors of hepatitis B in the Faculty of nursing, midwifery and health at Shahrekord Islamic Azad University in 2014.Materials and MethodsThis cross-sectional study was conducted with 300 students from the Faculty of nursing, midwifery and health at Shahrekord Islamic Azad University. The students answered questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…5,6 Iranian health sciences students have little knowledge regarding HBV and HCV infections, and previous studies have suggested interventions to increase this knowledge. [7][8][9] The World Health Organization wants to achieve the goal of viral hepatitis elimination by 2030. 10 One of the important steps for viral hepatitis elimination is increasing general knowledge, 11 and educational interventions are needed to increase knowledge and awareness.…”
Section: Major Articlementioning
confidence: 99%
“…5,6 Iranian health sciences students have little knowledge regarding HBV and HCV infections, and previous studies have suggested interventions to increase this knowledge. [7][8][9] The World Health Organization wants to achieve the goal of viral hepatitis elimination by 2030. 10 One of the important steps for viral hepatitis elimination is increasing general knowledge, 11 and educational interventions are needed to increase knowledge and awareness.…”
Section: Major Articlementioning
confidence: 99%
“…8 From this perspective, the fact that nursing is a profession with a larger number of women may be due to 14,15 In the academic context, the review of the responsibility of HEI regarding clarifications and actions directed to safety issues involving students during instructional practice, with emphasis on vaccination, has been analyzed. 16,17 A limitation of this study is the sample size and for this reason it is not possible to generalize the findings, but for the group studied we showed that academics who are…”
Section: Resuménmentioning
confidence: 82%
“…31 In another study, conducted among medical students in northern Iran, the levels of knowledge about HBV were reported higher in women than in men. 21 Due to the diversity of the findings among various studies, it seemed that the relationship between gender and levels of KAP parameters could not be concluded, i.e. it was not possible to find an exact relationship between levels of KAP and gender.…”
Section: Discussionmentioning
confidence: 99%